Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan di Kota Medan - Carine, Carine; Concetta, Cheryl; Violyne A. S; Situmorang, Irvan Rolyesh (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of leadership style on employee performance in Medan City. The research method applied is descriptive qualitative, using in-depth interviews, observations, and documentation as data collection techniques. The findings reveal that transformational and democratic leadership styles enhance employee motivation, job satisfaction, and productivity, while authoritarian leadership tends to reduce job satisfaction and negatively affect organizational target achievement. The conclusion emphasizes that adaptive, communicative, and empowering leadership styles are the most effective strategies to improve organizational performance in the face of increasingly complex business dynamics. Keywords: Employee, Leadership, Performance